Generation of Magnesium Pentafluoropropen-2-olate from Hexafluoroisopropanol and Synthesis of 2,2,4,4,4-Pentafluoro-3,3-dihydroxyketones - Hazlitt, Robert A. (J Org Chem, 2017)
2,2,4,4,4-Pentafluoro-3,3-dihydroxyketones are valuable precursors to difluoroenolates, following fragmentation during the release of trifluoroacetate; however, there are few synthetic strategies to prepare this unique class of compound. We have addressed this issue and report a mild, two-step synthesis of 2,2,4,4,4-pentafluoro-3,3-dihydroxyketones from aldehydes. Specifically, aldehydes are treated with pentafluoropropen-2-olate, generated from a new fragmentation of hexafluoroisopropanol with a mixed Mg/Li amide, to give pentafluoroalcohols. A subsequent oxidation with Dess-Martin periodinane provides the targets in good isolated yields.